Associação entre distúrbios do sono, cronotipos e bruxismo à dor em pacientes com neuralgia trigeminal ou neuralgia pós- herpética na região orofacial - Ressala Castro Souza (2023)
Neuropathic pain, originating from injury or dysfunction of the nervous somatosensory system, can affect the orofacial region, such as trigeminal neuralgia (TN) and postherpetic neuralgia (PHN). Despite the reports in the literature associating sleep disorders, evening chronotype, and activity of bruxism with chronic pain conditions, little is known about these associations with TN and PHN in the orofacial region. The objective of this work was to evaluate the association between sleep disorders, chronotypes, and bruxism to pain and psychosocial aspects in patients with TN and PHN in the orofacial region, compared to healthy control patients without chronic pain. After ethical approval, the obtained sample consisted of 25 individuals with TN and 14 individuals with PHN who were recruited at the outpatient clinics from the Pain Service of the Hospital das Clínicas at UFMG, private clinics, and the community in general; plus 55 control patients without cronic pain. Sociodemographic and pain data, sleep, chronotype, depressive and anxious symptoms, lifestyle, oral behaviors, and bruxism were collected; from which was performed a qualitative and quantitative statistical analysis. The pain data observed in this study are in line with the literature, for both the TN and PHN groups. For the TN group, pain shock is more prevalent in V2 (maxillary branch of the trigeminal nerve) and V3 (mandibular branch of the trigeminal nerve). For the PHN group, longer-lasting pain, burning pain is most often localized in V1 (ophthalmic branch of the trigeminal nerve). Concerning psychosocial factors, the TN group had a higher prevalence of sleep disorders and depressive disorder and worse socioeconomic condition. Higher scores for anxiety were correlated with a worse lifestyle in the PHN group, which also had a morning chronotype and a higher prevalence of parafunctional oral behaviors and anxiety. Considering the possible interference of pain in activities of daily living, the TN group showed greater interference than the other groups. With relation to lifestyle, more severe pain in the last 3 months was correlated with worse lifestyle in the TN group. In all groups, there was a correlation between a worse lifestyle and a greater presence of depressive symptoms. For bruxism, there was no difference between the groups regarding anxiety, depression, or lifestyle symptoms. Future studies are desirable for a better understanding of the circadian manifestations of orofacial neuropathy pain and its associations with chronotype, bruxism, and sleep disorders within the individual biopsychosocial context.